52.8k views
1 vote
Inverse of y equals 12 to the x

User Kin Cheung
by
4.7k points

1 Answer

4 votes

Answer:


f^(-1)(x) = log_(12)(y)

Explanation:

We have the following function

y = 12^x, and we need to find the inverse function.

To find the inverse function we should solve the equation for "x". To do so, first, we need to:

1. Take the logarithm in both sides of the equation:

lg_12 (y) = log _12 (12^x)

(Please read lg_12 as: "Logarithm with base 12")

From property of logarithm, we know that lg (a^b) = b*log(a)

Then:

lg_12 (y) = x*log _12 (12)

We also know that log _12 (12) = 1

Then:

x = log_12(y).

Then, the inverse of: y= 12^x is:


f^(-1)(x) = log_(12)(y)

User Emile Achadde
by
4.8k points